Implementation of Realistic Mathematics Education (RME) Approach to Elementary School Mathematics Problem Solving Ability - Wahyu Naldi; Tatang Herman; Masnur (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
Problem solving skills are indispensable asa part of 21st century skills. The lpw problem solving ability of students who have not been able to develop now knowledge actively in the classroom is caused because learning is still teacher-centered. The use of a learning approach can be a solution to train students’ problem solving abilities. This study aims to conduct a literatur review related to the implementation of the Realistic Mathematics Education (RME) approach in problem solving abilities in elementary schools. Data collection is done by documenting and reviewing all articles related to the Realistic Mathematics Education (RME) approach publish ed in the last 5 years. The results showed that the Realoistic Mathematic Education (RME) approach; 1) give real and practical math problems, 2) facilitate students’ understanding of problem solving skills, 3) Improving students’ cognitive and character aspects, and 4) increase students’ interest and learning outcomes. Form the date obtained, it can concluded that the Realistic Mathematics Education (RME) approach can improve mathematical problem solving abilities in elementary schools.